Reflectance Confocal Microscopy–Optical Coherence Tomography‐Guided Laser Ablation of Low‐Risk Basal Cell Carcinoma: A Long‐Term Prospective Follow‐Up Study - Noa Kremer; Miguel Cordova; Aditi Sahu; Larissa M. Pastore; Rachel Manci; Zaeem H. Nazir; Rozina Zeidan; Cristian Navarrete‐Dechent; Oriol Yélamos; Stephen W. Dusza; Nicusor Iftimia; Melissa Gill; et al. (Lasers in Surgery and Medicine, 2026)
ABSTRACT Objectives The primary objective was to evaluate the long‐term recurrence rate following RCM–OCT‐guided laser ablation of basal cell carcinomas (BCCs). The secondary objective was to assess patient‐reported outcomes, including willingness to undergo the treatment again, scar acceptability, and adverse effects. Methods A prospective cohort study evaluated 104 patients with 148 BCCs (2017–2021). Low risk BCC subtypes and with tumor depth of ≤ 300 µm were determined using RCM–OCT, and eligible lesions underwent same‐day Er:YAG laser ablation with immediate post‐treatment imaging to confirm clearance. Patients underwent clinical and RCM–OCT or RCM surveillance at 6 and 12 months and annually thereafter to assess recurrence. A patient‐reported questionnaire was conducted in 2023. Results Fifty‐eight lesions (39.2%) in 39 patients met the criteria for laser ablation. Most lesions were located on the trunk (29/58, 50.0%), with median tumor depth and lesion size of 200 µm and 9.8 mm, respectively. Immediate post‐ablation RCM–OCT demonstrated imaging‐defined complete clearance after a single session in 53/58 lesions (91.4%). Residual tumors (5/58, 8.6%) were successfully treated during the same visit. Fifty‐four of 58 lesions (93.1%) had at least 6 months of follow‐up (median 32 months; min/max 8–70). One recurrence occurred at 53 months and was successfully retreated, corresponding to 1.04 recurrences per 100 person‐years of follow‐up. The patient‐reported questionnaire response rate was 79.5% (31/39). Overall, 96.8% (30/31) reported acceptable scar appearance, 83.9% (26/31) were likely to choose laser ablation again (Score 1–2 of 5), and 9.7% (3/31) reported mild, transient side effects. Conclusions RCM–OCT‐guided Er:YAG laser ablation offers a “one‐stop” treatment approach for selected low‐risk BCCs, demonstrating low long‐term recurrence rates and high patient satisfaction.